PERATURAN PEMBAYARAN ZAKAT KEPADA INSTITUSI ZAKAT: SIKAP PENIAGA DAN KESANNYA TERHADAP GELAGAT PEMBAYARAN ZAKAT PERNIAGAAN - Saad, Ram Al Jaffri; Md Idris, Kamil; Bidin, Zainol (Jurnal Syariah, 2009)
This study is intended to explore and examine the businessmen’s attitude towards zakat regulation of the state of Kedah. In the first phase of the study, a small diverse group of businessmen gave us their view on this regulation using Likert procedures. After a thorough examination of the responses 24 items were included in the questionnaire for the second phase of the study. In the second phase, questionnaires were distributed to 700 businessmen. Analysis of the responses showed that businessmen’s attitude towards zakat regulation of the state of Kedah is complex and can be divided into five (5) components. Each component was named and treated as an individual variable in multiple regression analysis. Two components were found to have significant correlation to zakat compliance behaviour. This indicates that view on zakat is a complex latent variable, and it is proposed that for a study to gain informative understanding on zakat attitude, it should first decompose this variable.